Wetting Properties of the CO2-Water-Calcite System via Molecular Simulations: Shape and Size Effects - Silvestri, Alessandro; Ataman, E.; Budi, A.; Stipp, S.; Gale, Julian; Raiteri, Paolo (2019)
Assessment of the risks and environmental impacts of carbon geosequestration requires knowledge about the wetting behavior of mineral surfaces in the presence of CO2 and the pore fluids. In this context, the interfacial tension (IFT) between CO2 and the aqueous fluid and the contact angle, θ, with the pore mineral surfaces are the two key parameters that control the capillary pressure in the pores of the candidate host rock. Knowledge of these two parameters and their dependence on the local conditions of pressure, temperature and salinity is essential for the correct prediction of structural and residual trapping. We have performed classical molecular dynamics simulations to predict the CO2-water IFT and the CO2-water-calcite contact angle. The IFT results are consistent with previous simulations, where simple point charge water models have been shown to underestimate the water surface tension, thus affecting the simulated IFT values. When combined with the EPM2 CO2 model, the SPC/Fw water model indeed underestimates the IFT in the low pressure region at all temperatures studied. On the other hand, at high pressure and low temperature, the IFT is overestimated by ~5 mN/m. Literature data regarding the water contact angle on calcite are contradictory. Using our new set of force field parameters, we performed NVT simulations at 323 K and 20 MPa to calculate the contact angle of a water droplet on the calcite {10.4} surface in a CO2 atmosphere. We performed simulations for both spherical and cylindrical droplet configurations for different initial radii, to study the size dependence of the water contact angle on calcite in the presence of CO2. Our results suggest that the contact angle of a cylindrical water droplet on calcite {10.4}, in the presence of CO2, is independent of droplet size, for droplets with a radius of 50 Å or more. On the contrary, spherical droplets make a contact angle that is strongly influenced by their size. At the largest size explored in this study, both spherical and cylindrical droplets converge to the same contact angle, 38˚, indicating that calcite is strongly wetted by water.